(untitled) (Journal of Bio-Science, 2009)
Lemon cordial was prepared and its storage conditions were studied. The prepared cordial was kept in 250 ml sterilized glass bottles, sealed and stored at ambient temperature (22°- 37°C) for 360 days. The chemical composition, keeping quality and consumers acceptability of the product was analyzed at an interval of 15 days up to 120 days and then at an interval of 30 days upto360 days. Except vitamin C content, no noticeable change was observed during the storage. Key words: Lemon, Cordial, Citric acid, Ascorbic acid, Reducing sugar, Non-reducing sugar DOI:10.3329/jbs.v16i0.3755 J. bio-sci. 16: 125-127, 2008